The importance of immunophenotyping by flow cytometry in distinction between hematogones and B lymphoblasts - Wohlfahrt,Aline B. (2015)
Hematogones are normal B-lineage lymphoid precursors in the bone marrow. B lymphoblasts are immature neoplastic cells present in patients with precursor B-cell acute lymphoblastic leukemia (B-ALL). Hematogones and B lymphoblasts share characteristics, such as morphological similarity often indistinct and expression of the same antigens in immunophenotypic analysis. Increased numbers of hematogones in patients with B-ALL during regeneration of bone marrow after treatment for leukemia, in cases of disease relapse or marrow transplantation, may be subject to questions about the nature and prognosis of this immature cell. This article presents information about the morphological and immunophenotypic characteristics of B lymphoid precursors and verifies the relevance of immunophenotyping by flow cytometry (FC) in the distinction between those cells. This differentiation is essential to establish a correct prognosis and assist in medical decision about the most appropriate therapeutic scheme.